125k views
4 votes
Given the following functions: f(x) = x2 – 5 and g(x) = x - 3.
Find f(g(x))

1 Answer

3 votes

Answer:

f(g)x))= x^2 -6x +4

Explanation:

first, plug in g(x) into f(x): f(g)x)) =(x-3)^2 -5

then, you simplify the (x-3)^2 into (x-3)(x-3): f(g)x))= (x-3)(x-3) -5

when you distribute the two (x-3) you end up with: f(g)x))= x^2 -6x +9 -5

finally, you combine like terms and subtract 5 from 9 and your final answer is : f(g)x))= x^2 -6x +4

note: x^2 is x squared or exponent of 2

User Nathan Strutz
by
4.9k points